E-Module-Based Learning Media Training Physical Education To Teacher - Irvan Irvan; Agus Sutriawan; Muhammad Akbar Syafruddin; M Imran Hasanuddin; Muhammad Qasash Hasyim; Sufitriyono Sufitriyono (Universitas Teknokrat Indonesia, 2023)
The Lack Of Renewal Of Learning Media In The Learning Process Has A Significant Impact On Decreasing Student Learning Outcomes Because They Feel Bored In The Learning Process. This Is What Underlies The Implementation Of This PKM Activity. To Carry Out This Activity, Five Methods Are Used, Namely (1) Identification And Analysis Of Problems Experienced By Teachers. (2) Socialization In Compiling Online And Multimedia-Based Teaching Materials To Teachers To Be Developed In Learning. (3) Simulation Or Peer Teaching. (4) Learning Implementation Assistance. (5) Evaluation. Based On The Results Of Online-Based Learning Media Development Training In The New Normal Era At Pinrang 1 Public High School, It Can Be Seen That The Use Of The Flipping Book Application Has Been Combined Into Online Learning Using Other Applications, Namely 32% Have Used The Zoom Meeting Application, 4% Have Used Google Meet, 10 % Use The Canva Application, And 52% Use Blended Learning.